Diversity of Growth Patterns Probed in Live Cyanobacterial Cells Using a Fluorescent Analog of a Peptidoglycan Precursor - Zhang, Ju-Yuan; Lin, Gui-Ming; Xing, Wei-Yue; Zhang, Cheng-Cai (Frontiers in Microbiology, 2018)
Cyanobacteria were the first oxygenic photosynthetic organisms during evolution and were ancestors of plastids. Cyanobacterial cells exhibit an extraordinary diversity in their size and shape, and bacterial cell morphology largely depends on the synthesis and the dynamics of the peptidoglycan (PG) layer. Here, we used a fluorescence analog of the PG synthesis precursor D-Ala, 7-hydroxycoumarin-amino-D-alanine (HADA), to probe the PG synthesis pattern in live cells of cyanobacteria with different morphology. They displayed diverse synthesis patterns, with some strains showing an intensive HADA incorporation at the septal region, whereas others gave an HADA signal distributed around the cells. Growth zones covering several cells at the tips of the filament were present in some filamentous strains such as in Arthrospira. In Anabaena PCC 7120, which is capable of differentiating heterocysts for N2 fixation, PG synthesis followed the cell division cycle. In addition, an HADA incorporation was strongly activated from 12-15 h following the initiation of heterocyst development, indicating a thickening of the PG layer in heterocysts. The PG synthesis pattern is diverse in cyanobacteria and responds to developmental regulation. The use of fluorescent analogs may serve as a useful tool for understanding the mechanisms of cell growth and morphogenesis operating in these organisms.